2022
DOI: 10.2147/ppa.s345646
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in the Community During the COVID-19 Pandemic: A Qualitative Study to Understand Users’ Perspectives of Antibiotic Seeking and Consumption Behaviors in Bangladesh

Abstract: Introduction The COVID-19 pandemic is thought to have led to increased “inappropriate” or “unjustified” seeking and consumption of antibiotics by individuals in the community. However, little reference has been made to antibiotic seeking and using behaviors from the perspectives of users in Bangladesh during this health crisis. Purpose This study seeks to document how antibiotic medicines are sought and used during a complex health crisis, and, within different contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…It was found that the proportion of cephalosporins increased significantly in this study population in 2020 compared with 2019, which was supported by previous studies [ 44 , 50 ]. A recent study reported that the use of third-generation cephalosporins increased by 19% in 2020 compared with 2019 [ 38 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It was found that the proportion of cephalosporins increased significantly in this study population in 2020 compared with 2019, which was supported by previous studies [ 44 , 50 ]. A recent study reported that the use of third-generation cephalosporins increased by 19% in 2020 compared with 2019 [ 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…Although the impact of the COVID-19 outbreak on antibiotic consumption has been documented in some epidemiological studies, few of them were conducted among community populations because the reliable data on antibiotic use are largely limited to hospitalized patients [ 39 , 40 , 49 , 50 ]. Our study estimated that the risk of antibiotic use increased by 137% after the COVID-19 outbreak in China, while it was reduced to 72% after the control of the covariates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations